Therapeutic Applications of Antisense Oligonucleotides in Asthma and Allergy - Isidoro-Garcia, Maria; Davila, Ignacio (Recent Patents on Inflammation & Allergy Drug Discovery, 2007)
Antisense oligonucleotides represent a novel therapeutic approach for manipulation of gene expression in the treatment of respiratory diseases. This methodology is based on the use of synthetic oligonucleotides to inhibit the expression of a specific target gene by inhibiting the function of the corresponding messenger RNA. Inhaled antisense oligonucleotides are therapeutic alternatives in the treatment of respiratory diseases including allergic asthma; however development of this technology is at an early stage and critical questions related to design, biological activity, and target delivery still remain. The present review will discuss the current status of antisense technology and its application in asthma and allergy. It will be focused in some representative patents including considerations on the future clinical prospects.
Keywords: asthma